Evaluation of Some Management Options against Brinjal (Solanum melongena L.) Shoot and Fruit Borer (Leucinodes orbonalis [Guenee]) - Akter, Sharmin; Alam, MZ; Rahman, MM; Akanda, AM (The Agriculturists, 2017)
A field study was conducted to find out the effectiveness of five management options: i) Bacillus thuringiensis (Bt), ii) Tracer 45 SC (Spinosad), iii) Proclaim 5 SG (Emamectin benzoate), iv) mechanical control, and v) untreated control for suppressing brinjal shoot and fruit borer (BSFB) during-2012 at Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU). The treatments were arranged in a randomized complete block design with four replications. Results indicated that Tracer 45 SC performed the best in reducing 85.60% shoot infestation over control, which was followed by Proclaim 5 SG (76.62%), Bacillus thuringiensis (66.41%) and mechanical control (22.02%). The best performance of fruit infestation reduction over control by number and by weight was also obtained in Tracer 45 SC treated plots and reduced 88.80 and 89.46%, respectively. This was followed by Proclaim 5 SG (65.58 and 67.29%), Bacillus thuringiensis (52.63 and 54.28%) and mechanical control (31.88 and 19.04%). The highest yield of 11.20 t ha-1 and highest benefit cost ratio of 5.32 were recorded in Tracer 45 SC treated plots. The Agriculturists 2017; 15(1) 49-57